An Oxidation–Amidation Approach for the Synthesis of Glycuronamides. Issue 15 (3rd May 2016) - Lin, Sicheng; Ashmus, Roger A.; Lowary, Todd L.
Abstract: A route for the synthesis of glycuronamides via the intermediacy of 6‐ S ‐tolyl‐substituted glycosides and uronic acid thioesters, is reported. The route, which is compatible with a variety of carbohydrate residues and protecting groups, was used to synthesize the repeating unit of the E. coli K54 capsular polysaccharide. Abstract : A route for the synthesis of glycuronamides via the intermediacy of 6‐ S ‐tolyl‐substituted glycosides and uronic acid thioesters, is reported. The route, which is compatible with a variety of carbohydrate residues and protecting groups, was used to synthesize the repeating unit of the E. coli K54 capsular polysaccharide.